Phytonutrients in the promotion of healthspan: a new perspective - Jacquier, Emma F.; Kassis, Amira; Marcu, Diana; Contractor, Nikhat; Hong, Jina; Hu, Chun; Kuehn, Marissa; Lenderink, Christopher; Rajgopal, Arun (Frontiers in Nutrition, 2024)
Considering a growing, aging population, the need for interventions to improve the healthspan in aging are tantamount. Diet and nutrition are important determinants of the aging trajectory. Plantbased diets that provide bioactive phytonutrients may contribute to offsetting hallmarks of aging and reducing the risk of chronic disease. Researchers now advocate moving towards a positive model of aging which focuses on the preservation of functional abilities, rather than an emphasis on the absence of disease. This narrative review discusses the modulatory effect of nutrition on aging, with an emphasis on promising phytonutrients, and their potential to influence cellular, organ and functional parameters in aging. The literature is discussed against the backdrop of a recent conceptual framework which describes vitality, intrinsic capacity and expressed capacities in aging. This aims to better elucidate the role of phytonutrients on vitality and intrinsic capacity in aging adults. Such a review contributes to this new scientific perspectivenamelyhow nutrition might help to preserve functional abilities in aging, rather than purely offsetting the risk of chronic disease.